Pemanfaatan AI Pewakil Manajer dalam Implementasi Persetujuan Elektronis Berbasis SVM di Bidang SIM-SDM - Arman Yusuf (Prosiding SISFOTEK, 2019)
Artificial Intelligent (AI) has been popular and applied in many areas nowdays. Many features can be built upon machines by learning the characters human did, and later to inference the tasks based on what it has been learned before. Human tasks that have been learned by machine can then be utilized to replace human itself in repetitive tasks. In this research journal, the researcher utilizes one of the AI technology, Support Vector Machine (SVM) based Machine Learning to learn manager’s characters in the approval activities. This later will be used by machine that acts as a manager in making approvals. To learn the manager’s characters in approving activities, researcher will use R language; it regularly fetchs the data from database, learning the pattern and update the prediction model. It can be interfaced to external Human Resources (HR) module on Management Information System (MIS) to predict the approval status. With minimum effort, this model can be implemented in current MIS-HR that owned by the company to conduct the automatic approval process without manager’s interference. Thus, manager can conduct more strategic activities rather than only do the approval process.